Modeling and simulation of brushless AC motor using MATLAB/ SIMULINK and power system blockset / Mohd Sani Sahfie - Sahfie, Mohd Sani (2003)
This project presents the simulation and modeling of brushless ac motor using MATLAB/SIMULINK. The working principle of the model and simulation method is presented and the Power System Blockset (PSB) operation is described. MATLAB software is used to study the performance of brushless ac motor. The principle of the modeling method is presented, using block diagram in SIMULINK library to analyze the characteristics of the brushless ac motor. The results obtained with MATLAB software are presented to illustrate its possibilities.